Implementing Regional Early Warning Policy to Sustain Social Stability in North Minahasa Regency, Indonesia - Sammy C. S. Rompis; Fitri H. Mamonto; Steven V. Tarore (JR Education, 2026)
The study addresses the need for a more effective early detection and early prevention system in a socially plural district whose stability is strategically important for governance, investment, tourism, and intergroup harmony. Using a qualitative descriptive design, the original thesis collected data through in-depth interviews, observation, and document analysis involving officials of the Regional National Unity and Politics Agency (Kesbangpol), the Early Warning Community Forum (FKDM), interfaith actors, security institutions, district-level officials, and community leaders. The present article reorganizes the thesis into a full academic journal article and highlights the empirical findings through adapted tables and thesis-based figures. The findings indicate that the early warning policy has been implemented, but its performance remains suboptimal. Institutionally, Kesbangpol has carried out coordination, early detection, conflict mapping, and communication functions. However, implementation is constrained by limited human resources, insufficient budget, weak cross-sector coordination, limited analytical capacity, uneven public participation, and the absence of an integrated digital information system. The role of FKDM as a strategic community partner also remains underdeveloped due to limited training and operational support. At the same time, the policy benefits from several supportive factors, including local government commitment, a relatively strong regulatory foundation, collaboration with TNI and the Police, the influence of community and religious leaders, and local socio-cultural values that emphasize solidarity. The article argues that policy strengthening should move beyond formal compliance toward a collaborative, capacity-building, and digital governance model. It proposes an integrated strengthening strategy that combines institutional clarification, competency development, community-based reporting, and digital early warning infrastructure. The study contributes to the public administration literature by showing that regional early warning policy in plural local settings is not only a matter of legal design but also of implementation capacity, trust, inter-organizational coordination, and the ability to translate preventive governance into routine practice.